The IMPLEMENTATION OF CANVA AS A LEARNING MEDIA IN PROJECT-BASED ENGLISH LEARNING AT SMAN 1 BANJARAN: A QUALITATIVE STUDY - Brata, Gagan (NextGen Education Review Journal, 2025)
This research investigates the use of Canva in English language project-based learning (PBL) at SMAN 1 Banjaran. The study aims to understand how Canva influences students' engagement, creativity, and motivation in learning English. The research methodology includes observations and interviews with both teachers and students to gather comprehensive insights into their experiences with Canva in the PBL context. The findings reveal that the implementation of Canva significantly enhances the learning process. Teachers find Canva to be a user-friendly and versatile tool that facilitates the creation of visually appealing and engaging instructional materials. The integration of Canva into PBL encourages collaborative learning and improves students' digital literacy, critical thinking, and language skills. Students report increased motivation and enjoyment when using Canva, as well as enhanced creativity and the ability to express ideas more effectively. Teachers adopt various strategies to integrate Canva, including blended learning approaches, collaborative group projects, and project-based assessments. The use of Canva in PBL activities, such as poster creation, presentation design, and infographic development, provides students with opportunities to improve their vocabulary, writing, speaking, and presentation skills. The visual and interactive nature of Canva projects also serves as an effective formative assessment tool for teachers. Despite the positive outcomes, challenges such as limited access to technology and the need for ongoing teacher training were identified. Overall, the research highlights the potential of Canva as a valuable tool in enhancing the effectiveness of English language PBL and fostering a more engaging and interactive learning environment.